P-P06 Ward based goal directed fluid therapy (GDFT) in acute pancreatitis (GAP) trial: a feasibility randomised controlled trial [ISRCTN 36077283]. (16th December 2021) - Froghi, Farid; Soggiu, Fiammetta; Ricciardi, Federico; Vindrola-Padros, Cecilia; Floros, Lefteris; Martin, Daniel; Filipe, Helder; Varcada, Massimo; Gurusamy, Kurinchi; Bhattacharya, Satyajit; Fanshawe, Angela; Dolcea, Bogdan; et al.
Abstract: Background: Goal directed fluid therapy (GDFT) based on cardiac output assessment has been shown to reduce complications and improve survival for people undergoing major general surgery. There are no reports of cardiac output evaluation being used to optimise the fluid administration for patients with acute pancreatitis who are in a general surgery admission ward. Methods: The trial protocol has been published. 50 patients with acute pancreatitis were recruited, consented and randomly allocated to either ward-based GDFT with intravenous (IV) fluids administered based on stroke volume optimisation or standard ward care but with blinded cardiac output evaluation for 48 hours following hospital admission. Results: Over a period of 20 months 50 of 142 screened patients were recruited demonstrating that it was feasible to recruit into a randomised trial of this nature in ward patients with acute pancreatitis. 36 (72%) completed the allocated 48 hours of goal directed fluids with 10 (20%) discharged within 48 hours and 4 withdrawals (3 GDFT and 1 SC). Baseline characteristics of the groups were similar with only 3 participants having severe disease (6%, 1 GDFT, 2 SC). Similar volumes of IV fluids were administered in both groups (GDFT 5465 (1839) ml, SC 5211 (1745) ml). GDFT group had a lower heart rate, blood pressure and respiratory rate and improved oxygen saturations. GDFT was not associated with any harms. Complications of AP appear to be similar as was duration of stay in intensive care. Length of hospital stay was 5 (2.9) in GDFT and 6.3 (7.6) in SC groups. Conclusions: Ward GDFT is feasible and shows a signal of possible efficacy in acute pancreatitis in this early-stage study. A larger multi-site RCT is required to confirm clinical and cost effectiveness.